ANALYSIS OF FACTORS THAT INFLUENCE GREEN INNOVATION AMONG RUNNING EVENT ORGANIZER EMPLOYEES - Ristu Pangestu Titahing Gusti; Emilisa, Netania; Narendra, Rafli (LPPM STIE EKA PRASETYA, 2025)
This research examines the influence of Organizational Commitment, Innovative Work Behavior, Digital Innovation, and Green Innovation on running event organizer employees. The background to this research is driven by increasing awareness of the importance of environmentally friendly innovation along with the development of digital technology. The research method uses a quantitative approach by distributing questionnaires to 155 employees from PT Indonesia Muda Road Runner (IMRR) and PT Satu Nusa Internasional (SNI). Data were analyzed using Structural Equation Modeling (SEM). The research results show that Organizational Commitment has a positive influence on Innovative Work Behavior, and Innovative Work Behavior has a positive influence on Digital Innovation. However, there is no significant influence between Digital Innovation and Green Innovation. This research concludes that efforts to achieve Green Innovation require other supporting factors such as government support and organizational resources. This study provides insights for companies to increase organizational commitment and innovative behavior of employees to strengthen digital transformation and environmental sustainability.